The Role of Eucalyptus Oil in Crude Palm Oil As Biodiesel Fuel - Ena Marlina; Mochammad Basjir; Mitsuhisa Ichiyanagi; Takashi Suzuki; Gabriel Jeremy Gotama; Willyanto Anggono (Automotive Experiences, 2020)
Utilization of crude palm oils (CPO) as biodiesel faces difficulty due to their high level of viscosity. Mixing crude eucalyptus oils (CEO) with CPO may reduce the viscosity due to the presence of aromatic compounds in CEO. The single droplet analysis was performed to determine the characteristics of mixing CPO with the CEO. The results showed that the addition of CEO decreased the viscosity due to the presence of intermolecular attractions, thereby leading to more active molecules in the CPO-CEO mixture. Furthermore, the aromatic compound in the CEO helped in decreasing the CPO flash point, while the aromatic compound in the triglyceride molecule weakens the bonds between molecules. The addition of CEO to CPO tends to reduce the ignition delay due to the presence of cineol content in the CEO, which weakens the van der Waals bond in CPO.